Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2018
DOI: 10.1115/gt2018-76508
|View full text |Cite
|
Sign up to set email alerts
|

Design, Flow Simulation, and Performance Test for a Partial-Admission Axial Turbine Under Supercritical CO2 Condition

Abstract: The development of a 60-kWe turbo generator that uses supercritical carbon dioxide (sCO2) cycle technology at the lab scale is described herein. The design concept for the turbo generator involved using commercially available components to reduce the developmental time and to increase the reliability of the machine. The developed supercritical partial-admission CO2 turbine has a single-stage axial-type design with a 73-mm rotor mean diameter. The design of the sCO2 turbine uses impulse and partial admission to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The RGP (Real Gas Property) file is utilized to import the physical properties into CFX. Kang, 37 Han 38 and Cho 39 and Fairuz 22 also utilized this database in the research on SCO 2 turbine and seal, further got convincing results.…”
Section: Numerical Methodologymentioning
confidence: 94%
“…The RGP (Real Gas Property) file is utilized to import the physical properties into CFX. Kang, 37 Han 38 and Cho 39 and Fairuz 22 also utilized this database in the research on SCO 2 turbine and seal, further got convincing results.…”
Section: Numerical Methodologymentioning
confidence: 94%
“…Hence, the needful power of a DEA compressor is calculated based on its total number of active DEA (39) in which…”
Section: Compressormentioning
confidence: 99%
“…Partial admitting can be a major reason to reduce the efficiency of axial turbines with a high flow rate. It can exacerbate the instability of the flow through the turbine created by intermittent input flow particularly for supersonic impulse turbines 28 and can boost emission created by such a turbine 39 and causes structural problems for the turbine blades. 40 Using the inherent advantages of the DEA compressor, active detonation tubes are arranged to avoid partial admission input for the turbine.…”
Section: Diffuser and Turbinementioning
confidence: 99%
“…Utamura et al from Tokyo Institute of Technology has developed a 10 kW S-CO 2 power system as a lab-scale demonstration test plan [12], the designed turbine showed very low efficiency during the experimental study and only 110 W net power was generated and recorded [13]. The Korea Institute of Energy (KIER) has developed several S-CO 2 power systems since 2013, and the S-CO 2 turbines were the core factor reported limiting the system performance [14][15][16]. No net electrical power was successfully generated from their first test loop during experiments [16,17] and the updated new turbine also reported efficiency problem later [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Korea Institute of Energy (KIER) has developed several S-CO 2 power systems since 2013, and the S-CO 2 turbines were the core factor reported limiting the system performance [14][15][16]. No net electrical power was successfully generated from their first test loop during experiments [16,17] and the updated new turbine also reported efficiency problem later [15]. Maxence et al reported their S-CO 2 turbine, which was designed for a 50 kW power system in the European I-ThERM project, showed only 70% isentropic efficiency in numerical simulations [18].…”
Section: Introductionmentioning
confidence: 99%